The importance of floral damage for pollinator visitation in Alstroemeria ligtu L. - Botto Mahan, C.=700 1 Ojeda Camacho, M.
(Es, En)
Ilus., 11 ref.
Keywords: ASTROEMERIA; DAÑOS; FLORES; RELACIONES PLANTA ANIMAL; INSECTA; POLINIZADORES; CHILE; TASA DE VISITA DE POLINIZADORES; REVISTA CHILENA DE ENTOMOLOGIA